Implementasi Pendekatan Pentahelix dalam Melihat Tantangan dan Strategi Pengembangan Wisata Alam Telaga Madirda - Al Hamda Niqmatu Shalihah; Bagas Narendra Prahita; Atik Catur Budiati (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
This research aims to analyze the challenges faced by the community in developing the Telaga Madirda tourist attraction and to analyze the form of community involvement strategy in developing the Telaga Madirda tourist attraction through the Pentahelix approach. This research uses a qualitative descriptive approach. The data collection techniques used were in-depth interviews with village heads and heads of Bumdes as local residents and the forerunners of this tourism developer, observation and documentation. This research uses Keith Davis' theory of community participation with 3 indicators: individual mental and emotional involvement, motivation to contribute, and individual responsibility. Based on the results of this research, it shows that there are challenges in developing Telaga Madirda natural tourism, namely, the community does not have the motivation to move forward, there is a lack of skilled and professional human resources in Berjo village to develop tourism potential in the area, there are conflicts of interest and competing priorities. The next strategy carried out was the involvement of several parties or actors to develop Madirda Lake tourism. These actors can be Academics, Business, Community, Government, and Media or pentahelix.